Obesity and cardiovascular risk factors among internists in Indonesia - Nasution, Sally Aman; Sukrisman, Lugyanti; Ginanjar, Eka; Yunihastuti, Evy; Salim, Simon; Hidayat, Rudy; Muhadi, Muhadi; Bintoro, Siprianus Ugroseno Yudho; Tambunan, Asri Ludin; Purnomo, Hery Djagat; Aman, Andi Makbul; Ikhsan, Mohammad Robikhul; et al. (Frontiers in Endocrinology, 2025)
BackgroundObesity constitutes a significant global health concern, including in Indonesia, through increased risk of non-communicable diseases. Physicians, as healthcare providers, are not exempt from the impact of obesity toward general health, quality of life, and work performance. Among physicians, internists are particularly significant, as they assume primary responsibility for the management of obesity, thus the primary focus in this study. Obesity in internists is related to modifiable and non-modifiable risk factors. Therefore, identification of prevalence and risk factors of obesity in internists may aid in the improvement of their health through risk factor modification.MethodsA multicenter randomized cross-sectional study with a total sample of 1,064 internists across Indonesia is conducted to identify obesity profile and risk factors. Data were collected through questionnaire, physical examination, and biochemical testing and were analyzed using descriptive, bivariate, and multivariate analyses.ResultsThe prevalence of obesity in Indonesian internists is 61.4%, higher than the general population. Risk factors associated with obesity in Indonesian internists after adjusting for confounding factors were male gender (aOR 1.43, 95% CI 1.08-1.90), hypertension (aOR 1.88, 95% CI 1.26-2.79), history of diabetes mellitus (aOR 2.93, 95% CI 1.53-5.60), newly diagnosed diabetes mellitus (aOR 2.41, 95% CI 1.22-4.77), newly diagnosed prediabetes (aOR 1.70, 95% CI 1.26-2.30), and inadequate physical activity (aOR 1.85, 95% 1.15-2.98).ConclusionInternists are a special population differing in prevalence of obesity and its related risk factors compared with the general population, due to high professional demand impacting healthy lifestyle and behavior.